1993
DOI: 10.1101/gad.7.12b.2575
|View full text |Cite
|
Sign up to set email alerts
|

p53 domains: identification and characterization of two autonomous DNA-binding regions.

Abstract: We have investigated the DNA-binding, oligomerization, and trans-activation functions of isolated segments of murine p53. We find that p53 has two autonomous DNA-binding regions. One domain, from amino acid 280 to 390, forms stable tetramers and binds DNA nonspecifically. The biological significance, ff any, of this DNA-binding activity is not known. A second domain, from amino acid 80 to 290, does not form stable tetramers under stringent conditions but binds DNA both specifically and nonspecifically. The spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
206
1
2

Year Published

1994
1994
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(213 citation statements)
references
References 59 publications
(82 reference statements)
3
206
1
2
Order By: Relevance
“…All the modular regions of the transcriptional activator p53 were ®nally identi®ed when the central region of p53 protein containing the four conserved regions and the major mutation hot spots (residues 102 ± 292) (Pavletich et al, 1993;Bargonetti et al, 1993;Wang et al, 1993) was recognized as the speci®c DNA-binding domain.…”
Section: P53 a Sequence Speci®c Transactivatormentioning
confidence: 99%
“…All the modular regions of the transcriptional activator p53 were ®nally identi®ed when the central region of p53 protein containing the four conserved regions and the major mutation hot spots (residues 102 ± 292) (Pavletich et al, 1993;Bargonetti et al, 1993;Wang et al, 1993) was recognized as the speci®c DNA-binding domain.…”
Section: P53 a Sequence Speci®c Transactivatormentioning
confidence: 99%
“…p53 is a transcription factor that binds DNA in a sequence-speci®c manner with its central domain located between amino acids 102 and 292 (Pavletich et al, 1993;Bargonetti et al, 1993;Wang et al, 1993). Here we demonstrated that p120E4F contacts p53 in its DNA-binding region in vitro and residues from 256 ± 294 of p53 are involved in mediating the interaction (Figure 3).…”
Section: Discussionmentioning
confidence: 60%
“…Supporting this hypothesis, the two monomers, tr338 and tr298, are more impaired in their ability to bind to GST-E4FD350 (lanes 9 and 12, respectively). The interaction with tr298 was very weak, suggesting that the E4F-binding region is located near to the end of the core domain (mapped between residues 102 and 292; Pavletich et al, 1993;Bargonetti et al, 1993;Wang et al, 1993). In agreement with this assumption, a construct containing the tetramerization domain and the unspeci®c DNA-binding region but lacking the core domain (p53 Ct) was unable to interact (lane 18).…”
Section: E4f Associates With P53 In Vivomentioning
confidence: 65%
“…The importance of DNA binding for the tumor suppressor function of p53 is underscored by the fact that most of the mutations in the p53 gene found in tumors a ect the core domain of the p53 protein, which mediates sequence-speci®c DNA-binding Bargonetti et al, 1993;Wang et al, 1993;Prives et al, 1994). The resolution of the three-dimensional co-crystal structure of the p53 core domain bound to a single half-site of a p53 consensus sequence (Cho et al, 1994) then revealed that amino acid residues most frequently mutated in human cancer occupy positions critical for sequencespeci®c DNA binding (Cho et al, 1994;Arrowsmith and Morin, 1996;Soussi and May, 1996), further strengthening the hypothesis that DNA binding and transactivation are required for tumor suppression by p53.…”
Section: Introductionmentioning
confidence: 99%